Researcher Profile: An Interview with John E. Grable, Ph.D., CFP(R) - John Grable (Journal of Financial Therapy, 2014)
John E. Grable, Ph.D., CFP(R) teaches and conducts research in the Certified Financial Planner(TM) Board of Standards undergraduate and graduate programs at the University of Georgia. Prior to entering the academic profession, he worked as a pension/benefits administrator and later as a Registered Investment Advisor in an asset management firm. He served as the founding editor for the Journal of Personal Finance and as the co-founding editor of the Journal of Financial Therapy. His research interests include financial risk-tolerance assessment, psychophysiological economics, and financial planning help-seeking behavior. Dr. Grable has published nearly 100 peer-reviewed papers, co-authored two financial planning textbooks, and co-edited a financial planning and counseling scales book. He currently writes a quarterly column for the Journal of Financial Service Professionals, serves as academic consultant to the Journal of Financial Planning, and chair the CFP Board Council on Education.
Keywords: Grable; financial therapy; financial planning; academia